PERAN MATHLA’UL ANWAR MEMBENDUNG KAPITALISME PENDIDIKAN - Saepul Bahri; Muhajir Muhajir (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2023)
This study aims to analyze the role of Mathla'ul Anwar in efforts to stem the influence of capitalism in the education system in Indonesia. This type of research is qualitative, drawing on the role of Mathla'ul Anwar in stemming the influence of capitalism in the education system. Data collection was conducted through observation, in-depth interviews, and documentation. Data analysis is carried out through data collection, data presentation and conclusions, while data maturity uses source triangulation. The results show that education can shape the character and develop the potential of the younger generation, carried out through strict supervision measures, emphasis on quality and values, and the provision of scholarships and Mathla'ul Anwar has become the forefront in protecting the integrity of education.